Flow-reduced double valve actuation for improving the dynamic performance of electro-hydraulic servo drive. (January 2023) - Lu, Junting; Xie, Haibo; Chen, Yunmin; Yang, Huayong
Due to the negative correlation between the frequency response and the rated flow of the servo valve, there remains challenge to achieve high dynamic response of large-flow servo valve-controlled hydraulic systems under extreme operating conditions. Although the effective bandwidth of such system can be extended via various control methods, the inherent performance limit of hardware limits further improvement of the system dynamic response. In this paper, a flow-reduced double valve actuation strategy is proposed to improve the performance of electro-hydraulic servo drives. By reducing the actually used flow, the frequency response of the servo valve is enhanced due to the decreased hydraulic spring force and transient flow force acting on the spool. Two flow-reduced servo valves are adopted in parallel to meet large flow along with the improved dynamic performance. Simulation research is conducted and a servo valve-controlled shaking table with a specially designed valve block is used for experimental validation. Simulation and experimental results prove that the proposed strategy possesses better dynamic performance than the conventional single valve actuation.